Monoclonal antibodies capable of binding SARS-CoV-2 spike protein receptor-binding motif specifically prevent GM-CSF induction. Issue 1 (24th March 2021) - Qiang, Xiaoling; Zhu, Shu; Li, Jianhua; Chen, Weiqiang; Yang, Huan; Wang, Ping; Tracey, Kevin J; Wang, Haichao
Abstract: A severe acute respiratory syndrome (SARS)-like coronavirus 2 (SARS-CoV-2) has recently caused a pandemic COVID-19 disease that infected approximately 94 million and killed more than 2, 000, 000 people worldwide. Like the SARS-CoV, SARS-CoV-2 also employs a receptor-binding motif (RBM) of its envelope spike protein for binding the host angiotensin-converting enzyme 2 (ACE2) to gain viral entry. Currently, extensive efforts are being made to produce vaccines against a surface fragment of a SARS-CoV-2, such as the spike protein, in order to boost protective antibodies that can inhibit virus-ACE2 interaction to prevent viral entry. It was previously unknown how spike protein-targeting antibodies would affect innate inflammatory responses to SARS-CoV-2 infections. Here we generated a highly purified recombinant protein corresponding to the RBM of SARS-CoV-2, and used it to screen for cross-reactive monoclonal antibodies (mAbs). We found two RBM-binding mAbs that competitively inhibited its interaction with human ACE2, and specifically blocked the RBM-induced GM-CSF secretion in both human peripheral blood mononuclear cells and murine macrophage cultures. Our findings have suggested a possible strategy to prevent SARS-CoV-2-elicited "cytokine storm, " and revealed a potentially anti-inflammatory and protective mechanism for SARS-CoV-2 spike-based vaccines. Graphical Abstract: SARS-CoV-2 Spike Protein-reactive monoclonal antibodies specifically impaired the viral spike protein-induced GM-CSF secretion by human peripheral blood mononuclear cells.